Fikih Muamalah dan Era Industri 5.0: Menata Transaksi Ekonomi Digital Berbasis Syariah: Fiqh Al-Muamalah and the Industry 5.0 Era: Structuring Digital Economic Transactions on a Shariah Basis - M. Argha Isdhihar Al Qutsam Sandya Aziz; Muhammad Yazid (Litera Academica Publishing, 2025)
This study aims to analyze the dynamics of applying Islamic jurisprudence (fiqh muamalah) principles within the digital economy framework in the era of Industry 5.0. The research employs a qualitative descriptive approach through library research and content analysis of primary and secondary academic sources published between 2015 and 2025. The findings reveal that economic digitalization does not alter the essence of contractual principles in Islamic law; instead, it modifies their form and implementation to align with technological advancement. Core Islamic principles such as akad (contract), riba (usury), gharar (uncertainty), and maisir (speculation) remain the normative foundation guiding digital financial transactions toward justice, transparency, and ethical integrity. The study also highlights the crucial roles of financial authorities such as Indonesia’s Financial Services Authority (OJK) and Bank Indonesia, in collaboration with religious bodies like the National Sharia Council (DSN-MUI), in developing a digital financial ecosystem rooted in Islamic values. The synergy between regulators and religious authorities ensures that the digital economy evolves sustainably with ethical and equitable orientations. These findings affirm that fiqh muamalah possesses strong adaptability to technological innovation while maintaining the moral integrity of Islamic economic systems in the digital transformation era.